HUBUNGAN ANTARA KEPUASAN KERJA DAN KOMITMEN ORGANISASI DENGAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR PADA KARYAWAN PT X DI JAKARTA - Yohana, Corry (JRMSI - Jurnal Riset Manajemen Sains Indonesia, 2014)
The purpose of this study was to find out the relationship between job satisfaction and organizational commitment to organizational citizenship behavior (OCB) on employee of PT X in Jakarta. This study used a survey method with the correlational approach. Meanwhile sampling technique used is simple random technique. The samples were selected randomly. The results showed that: there is a positive relationship between job satisfaction and organizational commitment and organizational citizenship behavior (OCB) to the employees of PT X. Therefore if job satisfaction and organizational commitment of employees increases, the OCB will also increase. Keywords: job satisfaction, organizational commitment, organizational citizenship behavior (OCB)